Ligand-solvent compatibility: the unsung hero in the digestive ripening story - Shimpi, Jayesh R.; Chaudhari, Vijay Raman; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Digestive ripening (DR) is a process where a polydisperse nanocrystal (NC) system is converted into a monodisperse one with the aid of thermal heating of NCs in the presence of an excess surface-active organic ligand called digestive ripening agent (DRA) and a solvent. Here, we demonstrate that the solvent-DRA compatibility influences the final size and size distribution of the NCs in a significant manner. Accordingly, in this study, using the DR of gold NCs as the test case with alkanethiol (decanethiol/C10HT) and fluorinated thiol (1H,1H,2H,2H-perfluorodecanethiol/C10FT) as DRA's and toluene and alpha,alpha,alpha-trifluoro-toluene (TFT) and their combination as solvents, we clearly establish that alkanethiols result in best-quality NCs after DR in toluene while the fluorinated thiols provide reasonably monodispersed NCs in TFT. Our results also ascertain that even when DR is carried out in a mixture of solvents, as long as the compatible solvent is the major component, the DR process results in reasonably monodisperse NCs. As soon as the amount of uncompatible solvent exceeds a threshold limit, there is perceptible increase in the polydispersity of the NCs. We conclude that the polarity of the solvent, which affects the buildup of ligated atoms/clusters, plays a key role in controlling the size distributions of the NCs.

Ligands as ``Matchmakers'': alloying from a physical mixture of metal nanoparticle dispersions by digestive ripening - Shimpi, Jayesh R.; Prasad, V. Bhagavatula L. (Langmuir, 2022)
Digestive ripening (DR) of a physical mixture of different metal nanoparticles (NPs) in the presence of a suitable ligand is demonstrated to be a convenient way to obtain alloy NPs. The results show that the right choice of metal-ligand combination is extremely important for efficient alloying. The results are rationalized on the basis of hard soft acid base principles, and it is concluded that better alloying ensues if DR is carried out with soft ligands when soft metals are being used and hard ligands facilitate alloying between hard metals. On the other hand, when a physical mixture of hard-soft metals is taken, ligands with intermediate character work better. The results presented here could prove to be extremely valuable and open new avenues of making interesting alloy/intermetallic systems.

Influence of van der waals interactions between the alkyl chains of surface ligands on the size and size distribution of nanocrystals prepared by the digestive ripening process - Shimpi, Jayesh R.; Thomas, Rinto; Meena, Santosh Kumar; Prasad, Bhagavatula L. V. (Langmuir, 2023)
Thermal heating of polydispersed nanocrystals (NCs) with surface-active organic ligands in a solvent leads to the formation of monodispersed NCs, and this process is known as digestive ripening (DR). Here, by performing DR on Au NCs using different-chain-length amine and thiol ligands, we evidently show that ligands with C-12 chain length result in the formation of NCs with narrow size distributions when compared to C-8, C-16, and C-20 chain length ligands. Furthermore, our findings also show that in the case of alkyl thiol, the NC size remains more or less the same, while the size distribution gets altered significantly with the chain length. On the other hand, both size and size distribution are affected significantly when the alkyl amine chain length is varied. Fourier transform infrared (FTIR) studies indicate that the van der Waals (vdW) interactions are weakest when the amine with C-12 carbon chain is used as the DR agent, while in the case of thiols, molecules with C-8 and C-12 chain lengths have nearly the same vdW interactions (with C-12 slightly weaker than C-8), which are weaker than those of C-16 and C-20. Molecular dynamics (MD) simulation results corroborate the experimental observations and suggest that due to more defects in the alkyl chain, the C-8 and C-12 (amine as well as thiol) ligands are disordered and less stable on Au(111) and Au(100) surfaces. This could result in efficient etching and redeposition, making the ligands with C-8 and C-12 chain lengths the better DR agents.

Topological phases in nanoparticle monolayers: can crystalline, hexatic, and isotropic-fluid phases coexist in the same monolayer? - Bhattacharjee, Kaustav; Vaidya, Salil S.; Pathak, Tushar; Shimpi, Jayesh R.; Prasad, Bhagavatula L. V. (Soft Matter, 2023)
Topological phases are stable configurations of matter in 2-dimensions (2D) formed via spontaneous symmetry breaking. These play a crucial role in determining the system properties. Though a number of fundamental studies on topological phase transitions and topological defect dynamics have been conducted with model colloidal systems (typically microns in size), the same is lacking on nanoparticle monolayers (NPMLs, typically made of ligand-coated sub-ten nanometer particles). Here, we show that in an evaporation-driven self-assembly process, the three topological phases, namely crystalline, hexatic, and isotropic-fluid phases, can coexist within the same NPML. We associate this coexistence with the local variation in particle size, which can be described by a unique frequency parameter (p(25)), quantifying the fraction of NPs that has size deviation greater than or equal to 25% of the mean size (where the deviation,f is defined as f = ((|Size-mean|)/mean)). The p(25)-values for the three phases are distinctly different: crystalline arrangement occurs when p(25) < similar to 0.02, while a hexatic phase exists for 0.02 <= p(25) <= 0.1. For p(25) Z 0.1, the isotropic-fluid phase occurs. Following KTHNY-theory, we further numerically extrapolate the occurrence of each phase to the accumulated excess planar strain in the NPML due to the presence of various topological defects in the structures.